The Limits of Strategic Rationality: Ethics, Enterprise Risk Management, and Governance - Weitzner, David (Journal of business ethics, 2010)
This article explores the links between strategic goals, enterprise risk management, and ethics. We offer a typology of managerial attitudes toward strategic goals and rationality and explore the interaction between strategic and ethical decision making. In so doing, we offer a practical framework for managers to approach ethical dilemmas in the highly complex, volatile, and risky economy that we currently find ourselves in.